Bemerkung zu zwei Mischwesen in der späturukzeitlichen Rollsiegelmotivik - Lau, Daniel (Altorientalische Forschungen, 2018)
This contribution explores two exceptional motifs in Late Uruk glyptic that have been identified as demons. Introducing the concept of pareidolia in Mesopotamian archaeology, a different perception of these motifs is suggested, according to which they might present representations of two entangled human beings.